Personal Life Experience Shown in Irony: A Song Analysis - Theresia Arianti (International Journal of English Linguistics, Literature, and Education (IJELLE), 2023)
As songs are a means of conveying a message; thus, it is important to understand the lyrics of a song correctly. Irony is one way to embed a hidden message in a song. This study aims to investigate the irony contained in four songs: Welcome to Paradise, Welcome to My Life, Jesus of Suburbia, and Won’t be Home for Christmas. It also aims to examine what personal life struggle is shown in the irony contained. The findings show that three out of four songs examined represent the song writers’ personal life struggle related to childhood trauma. It is suggested that future studies do triangulation to this study to confirm the accuracy of the interpretation drawn.